Epistemologische Überzeugungen und innermathematische Experimente: Eine Interventionsstudie mit mathematisch interessierten Lernenden (mathematica didactica, 2022)
This article describes an intervention study on changing epistemological beliefs via working on intramathematical experiments. Ninety eleven- to fourteen-year-old students took part on a study to change their epistemological beliefs. This study took place in out-of-school learning location, called Junior Uni Wuppertal. As part of this intervention study it will be analyzed, how far a learning setting based on student experiments supports change of epistemological beliefs of interested and partially gifted students. The results show, that the mathematical epistemological beliefs of these students are naive at the beginning of the intervention and changed into more sophisticated beliefs after the intervention.